Greenness modified the association of PM2.5 and ozone with global disease burden of Alzheimer’s disease and other dementias - Wenjia Peng; Ting Liu (Scientific Reports)
Abstract Access to abundant greenness and low levels of air pollution have been widely recognized as contributing to a multitude of positive health outcomes. However, the empirical evidence elucidating the impact of air pollutants on the disease burden associated with dementia, as well as the potential modifying role of greenness, remains scarce. This ecological study aimed to explore the relationship between particulate matter with a diameter less than 2.5 micrometers (PM2.5) and ozone with the disease burden attributable to Alzheimer’s disease (AD) and other dementia, and further discuss the role of greenness on this association across 162 countries globally. We acquired data on the disease burden of AD and other dementias, along with air pollutant concentrations (PM2.5 and ozone), from the Global Health Data Exchange. We used the satellite-derived annual average normalized difference vegetation index (NDVI) and enhanced vegetation index (EVI) sourced from the MOD13A3 product, to quantify country-level exposure to greenness. A generalized linear mixed model based on penalized quasi-likelihood was employed for statistical analysis. Additionally, stratified analysis by greenness was performed to discuss the effect modification. In the fully adjusted model, we observed that per 10-unit increment in PM2.5 and ozone was positively associated with a 2.0% and 1.9%, 2.8% and 9.5%, 2.2% and 6.7% increased risk of incidence, death, and disability-adjusted life years (DALY) rate, respectively, for AD and other dementias. These associations were found to be more pronounced in countries with lower socio-demographic index and gross national income. In areas with high levels of greenness, both PM2.5 and ozone were observed to be associated with a diminished risk of disease burden related to AD and other dementias. Our findings provide evidence of a detrimental association between PM2.5 and ozone exposure and the disease burden of AD and other dementias, particularly in low-income countries. Moreover, our results suggest that higher levels of greenness exposure may have a modifying effect, mitigating the adverse impacts of air pollutants on these outcomes.